The synergistic effect of ultrasound and Er on the microstructure and mechanical properties of an Al–Cu alloy with high Fe content - Jinxin Cai; Li Zhang; Longfei Li; Guangxi Lu; Cong Xu; Ripeng Jiang; Yanfang Zhang; Lihong Wu; Shaokang Guan (Journal of Materials Research and Technology)
The large-sized needlelike iron-rich phases are detrimental to the grading utilization of the recycled Al alloys. In this paper, an effective method is put forward for the microstructural modification of an iron-containing Al–Cu alloy through simultaneously adding Er and applying ultrasound during solidification. The results show that coarse α-Al grains and a considerable amount of large-sized needlelike Al3Fe phase are observed in the sample neither adding Er nor applying ultrasound, while the size and continuity of acicular Al3Fe phase gradually decrease as the Er content increases. Meanwhile, α-Al grains are refined and a small portion of acicular Al3Fe phase transforms into platelike α-Fe phase with Er addition. Applying ultrasound alone, α-Al grains are refined by 21.1 % and the average length of needlelike Al3Fe phase is reduced by 33.5 % in comparison with the conventional sample. In contrast, synergistically applying ultrasound and adding 0.3 % Er significantly promotes the large-sized needlelike Al3Fe phase to transform into small-sized lamellate α-Fe phase, with grain refinement of 40.8 % and a 60.9 % reduction in the average length of needlelike Al3Fe phase. This is primarily ascribed to that cavitation and acoustic streaming facilitate the formation of dispersive Er-rich phases, which impedes the growth of coarsening needlelike Al3Fe phase and provides more sites as well as interface conditions beneficial to the nucleation of α-Fe phase. Correspondingly, the mechanical properties of the alloy sample with ultrasound and 0.3 % Er addition exhibit a substantial improvement in comparison to the conventional sample.